Reproductive cycles in Bos indicus cattle - Sartori, R.; Barros, C. M. [UNESP] (Elsevier B.V., 2011)
Several studies using transrectal ovarian ultrasonic scanning in Bos taurus (B. taurus) cattle and more recently in Bos indicus (B. Indicus) females evaluated the reproductive cycles of heifers and cows under different conditions. In general, B. indicus cattle have more follicles and more follicular waves during the estrous cycle and ovulate from smaller follicles than B. taurus. Consequently B. indicus females have smaller corpora lutea and it is assumed circulating concentrations of estradiol and progesterone are also less. However, these findings may vary depending on the nutritional status and regimen in which the animals are managed. Moreover, there are significant differences between B. taurus and B. indicus regarding follicle size at the time of deviation of the dominant follicle. These differences in ovarian function between B. indicus and B. taurus, e.g. greater antral follicle population are, probably, the main reasons for the great success of in vitro embryo production programs in Zebu cattle, especially in Brazil. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Follicle; Corpus luteum; Hormone; Estrus; Nutrition; Zebu